Reinsurance of health insurance for the informal sector - Dror David M. (The World Health Organization, 2001)
Deficient financing of health services in low-income countries and the absence of universal insurance coverage leaves most of the informal sector in medical indigence, because people cannot assume the financial consequences of illness. The role of communities in solving this problem has been recognized, and many initiatives are under way. However, community financing is rarely structured as health insurance. Communities that pool risks (or offer insurance) have been described as micro-insurance units. The sources of their financial instability and the options for stabilization are explained. Field data from Uganda and the Philippines, as well as simulated situations, are used to examine the arguments. The article focuses on risk transfer from micro-insurance units to reinsurance. The main insight of the study is that when the financial results of micro-insurance units can be estimated, they can enter reinsurance treaties and be stabilized from the first year. The second insight is that the reinsurance pool may require several years of operation before reaching cost neutrality.